2018
DOI: 10.5195/ijt.2018.6253
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies in Physical Therapy: Transitioning a "Hands-On" Approach into a Virtual Platform

Abstract: Technology is expanding at an unprecedented rate. Because patients value the speed and convenience of the internet, there is an increasing demand for telemedicine. Practitioners must therefore adapt their clinical skills to evolving online technologies. This paper presents a series of three case studies in which a physical therapist first assessed and treated musculoskeletal disorders via a live, secure video. The basis of the mechanical assessment was observation of movement rather than palpation. In each cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
8
1
1
Order By: Relevance
“…41 However, telemedicine has been identified as an effective tool to manage the comprehensive care of a patient using Internet-based, realtime video to assess and treat musculoskeletal disorders. 42 Despite the perceived self-limitation of the technology, the accuracy of diagnosis in our study was 90.9%, which was on par with previous research 43 in which 93% of participants had the same diagnosis when conducting a physical therapy assessment face-to-face or via telemedicine. These studies were both completed using cases requiring the physical examination of a sprained ankle, which warrants the need for future investigations relative to orthopedic exams for other more complex regions such as the shoulder and low back.…”
Section: Telemedicine Skillscontrasting
confidence: 40%
“…41 However, telemedicine has been identified as an effective tool to manage the comprehensive care of a patient using Internet-based, realtime video to assess and treat musculoskeletal disorders. 42 Despite the perceived self-limitation of the technology, the accuracy of diagnosis in our study was 90.9%, which was on par with previous research 43 in which 93% of participants had the same diagnosis when conducting a physical therapy assessment face-to-face or via telemedicine. These studies were both completed using cases requiring the physical examination of a sprained ankle, which warrants the need for future investigations relative to orthopedic exams for other more complex regions such as the shoulder and low back.…”
Section: Telemedicine Skillscontrasting
confidence: 40%
“…One observational study [ 48 ] and the remaining case studies/series included in this review, investigated the use of telehealth assessments for participants with either low back pain [ 48 , 53 , 75 ], gender health concerns (pelvic dysfunction or post-partum support) [ 44 , 57 ] or cancer care [ 42 ]. Of these studies, one study reported telehealth consultation lengths ranging from 3-21 minutes (mean 8.5 minutes) with consultation time devoted to pain, administrative issues, and actions, ie, bookings and advice on physical activity [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were performed in the United States of America. [21][22][23][24][25][26] Four studies were performed in Australia [27][28][29][30] and three in the United Kingdom. [31][32][33] Two studies each were performed in Sweden, 34,35 Spain 36,37 and Canada.…”
Section: Countries Where Studies Were Performedmentioning
confidence: 99%